Masked inefficacy of arterial hypertension treatment: prevalence and predictors - M. I. Smirnova; R. G. Oganov; M. V. Gorbunov; A. D. Deev; G. F. Andreeva (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To assess the prevalence of masked inefficacy of arterial hypertension treatment (AH MTI) and its predictors in various clinical groups and for various blood pressure (BP) control strategies, in order to evaluate the true effectiveness of antihypertensive therapy (AHT). Material and methods. AHT effectiveness was assessed in two groups of the patients with Stage I-II AH (n=219 and n=39), by comparing the ratios of clinical (cl) to ambulatory (a) BP parameters. AH MTI was defined as elevated aBP and target clBP levels during AHT. The potential predictors of AH MTI included gender, age, body mass index (BMI), anamnestic data, frequency of the clinical visits to measure BP, quality of life (QoL) parameters (GWBQ questionnaire), circadian BP profile, orthostatic BP, and ECG signs of left ventricular hypertrophy (LVH). Results. AH MTI prevalence in Groups I and II was 11,0-15,7 % and 22,6-58,1 %, respectively, depending on the definition used. The groups were significantly different in terms of age, BMI, and QoL questionnaire III and VI domains. According to the regression analysis results, in Group I AH MTI was associated with QoL questionnaire II, V, and VI domains, baseline parameters of 24-hour BP monitoring, 24-hour systolic BP (SBP) variability, minimal daytime levels of mean BP, and metoprolol and atenolol therapy. In Group II, AH MTI was predicted by age, BMI, previously administered AHT, alcohol consumption, orthostatic SBP levels, Sokolow-Lyon index, Cornell voltage and Cornell product, Gubner index, and QoL questionnaire I, IV, and VI domains. Conclusion. AH MTI prevalence is associated with some baseline characteristics of the patients and the character of AHT. Due to regression to the mean, AH MTI prevalence could increase substantially when clBP parameters are measured more often.